튜터링 프로그램 참여 대학생의 전공별 학습몰입 영향요인 분석 - 김옥분(Kim Okboon); 김혜진(Kim Hyejin) (교양교육연구, 2017)
본 연구는 튜터링 프로그램에 참여한 대학생 튜티를 대상으로 전공계열별로 그들의 학습몰입에 미치는 영향 요인과 변인간 상호상관을 분석함으로써 대학생의 학습몰입을 높일 수 있는 방안을 제시하는 것을 목적으로 한다. 본 연구 목적을 달성하기 위하여 2015년 서울 소재 S 대학과 H 대학에서 튜터링 프로그램에 자발적으로 참여한 튜티 174명(인문사회계열 110명, 공대자연계열 64명)을 대상으로 학습몰입, 인지역량, 대인관계, 창의적 인성 및 학습동기에 대한 검사를 실시하였다. 수집된 자료는 SPSS 18.0 프로그램을 활용하여 중다회귀분석과 상관분석을 실시하였다. 분석 결과, 인문사회계열 튜티의 학습몰입에 유의미한 영향을 미치는 요인은 학습목표 지향성, 창의적 성향, 자기효능감이었으며, 공대자연계열 튜티의 학습몰입에는 초인지, 고등사고, 학습목표 지향성이 유의미한 영향을 미치는 것으로 나타났다. 본 연구결과는 인문사회계열 대학생의 경우 과제를 잘 수행할 수 있다는 기대감과 만족감을 느낄 수 있도록 결과보다 과정에 초점을 둔 교육기회를 제공하고, 긍정적 피드백을 제공하는 교육이 바람직함을 시사한다. 공대자연계열 학생들의 경우에는 자신의 과제를 전체에서 부분으로 스스로 점검하고 검토할 수 있도록 기회를 제공하며, 실제적인 문제를 토대로 분석적 사고와 종합적 사고능력이 발휘될 수 있는 프로젝트 중심의 학습을 제공하는 교육환경이 효과적일 수 있음을 시사한다. 본 연구는 자발적으로 튜터링 팀을 구성하여 프로그램에 참여한 튜티들의 개인 특성을 전공별로 나누어 살펴봄으로써 교육현장에서 적용 가능한 구체적이고 상세한 정보를 제공해 준다는 점에서 의의가 있다. The purpose of this study was to identify the predicting variables of learning flow of college students who participated voluntarily in peer tutoring program according to their major groups. The subjects were 174 tutees (110 whose majors are humanities and social sciences, 64 whose majors are engineering and natural sciences) at the two private universities in Seoul during two semesters of 2015. They completed the scales such as learning flow, cognitive thinking competence, interpersonal relationship, creative personality, and motivation. The collected data were analyzed by multiple regression analysis and correlation coefficient using SPSS 18.0. Results can be summarized as follows: first, for tutees with humanities and social sciences majors,` learning goal orientation, creative personality and self-efficacy have significant influences on tutees’ learning flow. Second, tutees’ meta cognition, higher thinking, and learning goal orientation were found to be variables affecting learning flow significantly for the students with engineering and natural sciences majors. These results suggest that educational opportunities which focus on process rather than outcome and positive feedback would be better to be provided for students with humanities and social sciences majors. This study provides educators with useful informations for promoting and developing self-directed learning or learning flow program involving tutoring programs in higher education. KCI Citation Count: 3